Cross-Border Trade Disputes: A Comparative Analysis of Indonesia and Australia - Riyanto, R Benny; Laryea, Emmanuel; Fibrianti, Nurul; Latifiani, Dian (Journal of Indonesian Legal Studies, 2024)
This comparative analysis delves into the intricate landscape of cross-border trade disputes, focusing on Indonesia and Australia. As two significant players in the global trade arena, understanding their dispute resolution mechanisms is crucial for fostering bilateral and multilateral trade relationships. The study examines the legal frameworks, institutional mechanisms, and cultural factors influencing trade dispute resolution in both countries. Indonesia's approach may reflect its unique socio-political context, while Australia's system could showcase its commitment to transparency and adherence to international trade norms. Key aspects explored include the role of governmental bodies, such as trade ministries and dispute settlement panels, as well as the utilization of alternative dispute resolution methods like arbitration and mediation. Moreover, the analysis delves into the effectiveness and efficiency of these mechanisms in resolving disputes promptly while maintaining fairness and equity for all parties involved. Comparisons are drawn between Indonesia and Australia in terms of legal precedents, enforcement mechanisms, and the level of stakeholder engagement in the dispute resolution process. Additionally, cultural nuances and historical contexts are considered to understand how these factors shape the negotiation and resolution of trade conflicts. By synthesizing these insights, the study aims to provide policymakers, trade practitioners, and academics with a comprehensive understanding of the strengths and weaknesses of each country's approach to cross-border trade dispute resolution. Ultimately, it seeks to contribute to the development of best practices and strategies for enhancing trade relations and promoting economic cooperation between Indonesia and Australia, as well as other nations globally.